<< Chapter < Page Chapter >> Page >
  • Let b = 1. Then f ( x ) = 1 x = 1 for any value of x .

To evaluate an exponential function with the form f ( x ) = b x , we simply substitute x with the given value, and calculate the resulting power. For example:

Let f ( x ) = 2 x . What is f ( 3 ) ?

f ( x ) = 2 x f ( 3 ) = 2 3   Substitute  x = 3. = 8   Evaluate the power .

To evaluate an exponential function with a form other than the basic form, it is important to follow the order of operations. For example:

Let f ( x ) = 30 ( 2 ) x . What is f ( 3 ) ?

f ( x ) = 30 ( 2 ) x f ( 3 ) = 30 ( 2 ) 3 Substitute  x = 3. = 30 ( 8 )   Simplify the power first . = 240 Multiply .

Note that if the order of operations were not followed, the result would be incorrect:

f ( 3 ) = 30 ( 2 ) 3 60 3 = 216,000

Evaluating exponential functions

Let f ( x ) = 5 ( 3 ) x + 1 . Evaluate f ( 2 ) without using a calculator.

Follow the order of operations. Be sure to pay attention to the parentheses.

f ( x ) = 5 ( 3 ) x + 1 f ( 2 ) = 5 ( 3 ) 2 + 1 Substitute  x = 2. = 5 ( 3 ) 3 Add the exponents . = 5 ( 27 ) Simplify the power . = 135 Multiply .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Let f ( x ) = 8 ( 1.2 ) x 5 . Evaluate f ( 3 ) using a calculator. Round to four decimal places.

5.5556

Got questions? Get instant answers now!

Defining exponential growth

Because the output of exponential functions increases very rapidly, the term “exponential growth” is often used in everyday language to describe anything that grows or increases rapidly. However, exponential growth can be defined more precisely in a mathematical sense. If the growth rate is proportional to the amount present, the function models exponential growth.

Exponential growth

A function that models exponential growth    grows by a rate proportional to the amount present. For any real number x and any positive real numbers a   and b such that b 1 , an exponential growth function has the form

  f ( x ) = a b x

where

  • a is the initial or starting value of the function.
  • b is the growth factor or growth multiplier per unit x .

In more general terms, we have an exponential function , in which a constant base is raised to a variable exponent. To differentiate between linear and exponential functions, let’s consider two companies, A and B. Company A has 100 stores and expands by opening 50 new stores a year, so its growth can be represented by the function A ( x ) = 100 + 50 x . Company B has 100 stores and expands by increasing the number of stores by 50% each year, so its growth can be represented by the function B ( x ) = 100 ( 1 + 0.5 ) x .

A few years of growth for these companies are illustrated in [link] .

Year, x Stores, Company A Stores, Company B
0 100 + 50 ( 0 ) = 100 100 ( 1 + 0.5 ) 0 = 100
1 100 + 50 ( 1 ) = 150 100 ( 1 + 0.5 ) 1 = 150
2 100 + 50 ( 2 ) = 200 100 ( 1 + 0.5 ) 2 = 225
3 100 + 50 ( 3 ) = 250 100 ( 1 + 0.5 ) 3 = 337.5
x A ( x ) = 100 + 50 x B ( x ) = 100 ( 1 + 0.5 ) x

The graphs comparing the number of stores for each company over a five-year period are shown in [link] . We can see that, with exponential growth, the number of stores increases much more rapidly than with linear growth.

Graph of Companies A and B’s functions, which values are found in the previous table.
The graph shows the numbers of stores Companies A and B opened over a five-year period.

Notice that the domain for both functions is [ 0 , ) , and the range for both functions is [ 100 , ) . After year 1, Company B always has more stores than Company A.

Now we will turn our attention to the function representing the number of stores for Company B, B ( x ) = 100 ( 1 + 0.5 ) x . In this exponential function, 100 represents the initial number of stores, 0.50 represents the growth rate, and 1 + 0.5 = 1.5 represents the growth factor. Generalizing further, we can write this function as B ( x ) = 100 ( 1.5 ) x , where 100 is the initial value, 1.5 is called the base , and x is called the exponent .

Questions & Answers

the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
tan hyperbolic inverse (x+iy)=alpha +i bita
Payal Reply
prove that cos(π/6-a)*cos(π/3+b)-sin(π/6-a)*sin(π/3+b)=sin(a-b)
Tejas Reply
why {2kπ} union {kπ}={kπ}?
Huy Reply
why is {2kπ} union {kπ}={kπ}? when k belong to integer
Huy
if 9 sin theta + 40 cos theta = 41,prove that:41 cos theta = 41
Trilochan Reply
what is complex numbers
Ayushi Reply
Please you teach
Dua
Yes
ahmed
Thank you
Dua
give me treganamentry question
Anshuman Reply
Solve 2cos x + 3sin x = 0.5
shobana Reply
Practice Key Terms 4

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask